ИНГЛИС ҲӘМ ҚАРАҚАЛПАҚ ТИЛЛЕРИНДЕ АХРОМАТИКАЛЫҚ РЕҢЛЕРДИҢ ФУНКЦИОНАЛ-СЕМАНТИКАЛЫҚ СЫПАТЫ - Джумамуратов, К. (FAN va JAMIYAT, 2024)
The article analyzes achromatic colors, in particular phraseological units related to the color "white". Phraseological units related to achromatic colors in English and Karakalpak languages are also studied by comparison.